The positive and negative significance of the star in the Mesopotamian civilization: a semiotic study - Yaseen, Ghassan Taha; Hamid Hasani, Juhaena (2012)
This study deals with semiotic findings about the significance of the stars in its dual contradictory aspects, both the positive and the negative as found in the Mesopotamian civilization. Stars, in mid nights have been the means of guidance both on the land and the sea. People make use of them to determine the time (the day, the month etc), as well as the inference of knowledge through which the road map came into existence and widened the intellectual channels in reading fortunes, horoscopes and characterized as signs or benchmarks by which its consistent rhetorical practices became marketable among people until today. This study is quite different from the previous studies in the sense that it deals with two significant aspects which are: First; It focuses on the structural transformation of the significance of the star between two contradictory forms (the positive and the negative), beginning with the first culture dating back to the period of pre-history until the modern Babylonian age during which Mesopotamian civilization flourished. Moreover, this study attempts to present a modification and amendments on the findings of the previous researches,especially those relating to archeological concepts during the formation of the symbols. It dates back to the Sumerian era, which followed the advent of writing. The second significance of the study which seems to be the most important from the technical aspect is the structural content which has materialized from the symbolic correlation. It really considered the star as the result of the addition of whatever looks like the numerical seven only, whether the star is five angled or eight angled. The issue here is not based on type; rather it is based on formation of the significance of the star and the fact that it is fully integrated with the text. From this we can discern the civilization significance and meaning and performance of Mesopotamia through history. Hence, we are now in front of a new conclusion which we deduce as a figure out of many in our study entitled: “The Forms Systems in Mesopotamian Plastic Arts the Era Before Writing a Semiotic Study"; The most truthful factor we must mention here is that the stars are so vital in the life of people that God Almighty named them after one of the chapters of the holy Qur'an.